Basic Life-Support Learning in Undergraduate Students of Sports Sciences: Efficacy of 150 Minutes of Training and Retention after Eight Months - Aranda-García, Silvia (Int J Environ Res Public Health, 2019)
Several professional groups, which are not health professionals, are more likely to witness situations requiring basic life support (BLS) due to the nature of their job. The aim of this study was to assess BLS learning after 150 min of training in undergraduate students of sports science and their retention after eight months. Participants trained on BLS (150-min session: 30 theory, 120 practice). After training (T1) and after 8 months (T2), we evaluated their performance of the BLS sequence and two minutes of cardiopulmonary resuscitation (CPR). At T1, the 23 participants presented a mean score of 72.5 ± 21.0% in the quality of the CPRs (compressions: 78.6 ± 25.9%, ventilation: 69.9 ± 30.1%). More than 90% of the participants acted correctly in each step of the BLS sequence. At T2, although the overall quality of the CPR performed did not decrease, significant decreases were observed for: correct hand position (T1: 98.2 ± 8.8, T2: 77.2 ± 39.7%), compression depth (T1: 51.4 ± 7.9, T2: 56.0 ± 5.7 mm), and compression rate. They worsened opening the airway and checking for breathing. In conclusions, participants learned BLS and good-quality CPR after the 150-min training session. At eight months they had good retention of the BLS sequence and CPR skills. Training on airway management and the position of the hands during CPR should be reinforced.